Crafting Cancer-Fighting Wonders: Synthesis, Characterization, and Evaluation of a Novel Thiazole Derivative Targeting EGFR - Sapkale, Prabodh Vinayak; Patil, Avinash Vishwanath (Indian Journal of Pharmaceutical Education and Research, 2026)
Aim: The development of novel thiazole derivatives, namely PVS 3.1, 3.2, 3.3, and 3.4, marks a significant advancement in the field of anticancer drug discovery. These compounds were synthesized using an efficient, time-saving synthetic route that overcomes the limitations of conventional methods, which are often laborious, time-intensive, and costly. The new approach reflects a considerable step forward in the streamlining of drug development processes. Materials and Methods: The cytotoxic potential of the synthesized derivatives was systematically evaluated against two human cancer cell lines MCF-7 (breast adenocarcinoma) and A431 (epidermoid carcinoma of the lung) using the standard MTT assay. This colorimetric assay enabled the assessment of cell viability and revealed that all four compounds exhibited substantial inhibitory effects on cancer cell proliferation. The observed activity suggests promising antiproliferative properties inherent in the thiazole scaffold. Results: To further explore the molecular mechanism underlying the anticancer activity, the compounds were assessed for their inhibitory effect on the L858R/T790M double mutant form of the Epidermal Growth Factor Receptor (EGFR) tyrosine kinase. This specific EGFR mutation is commonly associated with acquired resistance to existing EGFR-targeted therapies and contributes significantly to uncontrolled cancer cell growth. Inhibitory activity of the PVS compounds against this mutant enzyme highlights their potential utility in overcoming resistance mechanisms and targeting key signaling pathways involved in tumor progression. Discussion: The findings suggest that the synthesized compounds exert a dual mode of action by both inducing cytotoxic effects in cancer cells and inhibiting a critical molecular target implicated in cancer development and drug resistance. Although these preliminary results are promising, further investigations including mechanistic studies, in vivo efficacy, toxicity profiling, and pharmacokinetic assessments are essential to fully establish the therapeutic potential of these thiazole derivatives. Conclusion: Overall, this study introduces a promising class of molecules with potential utility in the development of new anticancer therapies, particularly for treatment-resistant cancers. The dual-action capability of these compounds may offer a strategic advantage in designing multifaceted therapeutic approaches.
Keywords: Thiazole derivatives; Anticancer activity; MTT assay; EGFR tyrosine kinase; L858R/; T790M mutation; Drug resistance; Cytotoxicity; Targeted therapy; Cancer cell lines; Dual-mode; action